ASSESSMENT AND MAPPING OF DESERTIFICATION USING SOIL QUALITY INDICATORS FOR SOME PARTS OF IRAQ - & Azeez, Qadir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted to assess desertification for dry lands in some parts of Iraq. The study area located between longitudes 43025- 41" - 460 28- 01" E and latitudes 340 18- 35" - 360 20- 56" N with an area of 26500Km2which include some parts of the governorates of Sulaimani, Diyala, Kirkuk, and Erbil in Iraq.  Eighty nine surface soil samples were taken, air dried, sieved through a 2 mm sieve and then analyzed for some physical and chemical properties.   Desertification is assessed according to Mediterranean Desertification and Land Use model (MEDALUS). ArcGIS 10.2 was used to analyze and prepare the layers of soil quality maps. In turn the geometric mean of all six quality maps was used to generate a single desertification status map .In calculating the weight of the soil quality indicator SQI it seems that it was divided into two classes, firstly, class 2(moderate quality) with an area of 25147 km2, which occupied 95% of the study area and the rest is class3 (low quality) with an area of ​​1309 km 2 which equal to 5% of the total area.